ABCC3 and OCT1 genotypes influence pharmacokinetics of morphine in children. (July 2014) - Venkatasubramanian, Raja; Fukuda, Tsuyoshi; Niu, Jing; Mizuno, Tomoyuki; Chidambaran, Vidya; Vinks, Alexander A; Sadhasivam, Senthilkumar
Aim: Large interindividual variability in morphine pharmacokinetics could contribute to variability in morphine analgesia and adverse events.Methods: Influence of weight, genetic polymorphisms, race and sex on morphine clearance and metabolite formation from 220 children undergoing outpatient adenotonsillectomy was studied. A nonlinear mixed effects model was developed in NONMEM to describe morphine and morphine glucuronide pharmacokinetics.Results: Children with ABCC3 -211C>T polymorphism C/C genotype had significantly higher levels of morphine-6-glucuronide and morphine-3-glucuronide formation (∼40%) than C/T+T/T genotypes (p < 0.05). In this extended cohort similar to our earlier report, OCT1 homozygous genotypes (n = 13, OCT1*2–*5/*2–*5 ) had lower morphine clearance (14%; p = 0.06), and in addition complementing lower metabolite formation (∼39%) was observed. ABCB1 3435C>T TT genotype children had lower levels of morphine-3-glucuronide formation though no effect was observed on morphine and morphine-6-glucuronide pharmacokinetics.Conclusion: Our data suggest that besides bodyweight, OCT1 and ABCC3 genotypes play a significant role in the pharmacokinetics of intravenous morphine and its metabolites in children. Original submitted 12 April 2014; Revision submitted 20 June 2014